Інформаційний потенціал реалізації економічних завдань державного управління - Яковенко, Р. В.; Зайченко, В. В.; Yakovenko, R.; Zaychenko, V. (РВЛ ЦНТУ, 2020)
У тезах досліджується інформаційний фактор у системі державного управління в розрізі можливості впливу на ціни. Визначено сутність та роль інформації в сучасному світовому господарстві з орієнтацію на країни – лідери світового розвитку. Наведено характеристику економічної системи України, яка, так само як і більшість країн колишнього СРСР, характеризується олігархічним укладом, поєднанням економічної та політичної влади, але з декларуванням ринкових цінностей. Визначено принципи побудови та організації системи державного управління та державного регулювання економіки в Україні, проаналізовано домінування особистого матеріального інтересу окремих представників системи державного управління над суспільними та національними інтересами. This thesis investigates the information factor in the system of public administration in terms of the possibility of influencing prices. The essence and role of information in the modern world economy from the orientation towards the countries – leaders of world development are determined. The characteristics of the economic system of Ukraine, which, like most countries of the former USSR, is characterized by an oligarchic structure, a combination of economic and political power, but with the declaration of market values, is described. The principles of construction and organization of the system of state administration and state regulation of the economy in Ukraine are determined, the domination of personal financial interests of some representatives of the system of state administration over social and national interests is analyzed.
Information potential of realization of economic tasks of public administration
Keywords: інформація; державне управління; інформаційна бульбашка; витрати; комунальні послуги; information; public administration; information bubble; costs; utilities